World Trade Organisation (Wto) In India: Understanding the impact of WTO on the Indian economy and developing an effective policy line (Journal of Advances and Scholarly Researches in Allied Education, 2013)
This research is an effort to understand the impact ofWTO on Indian economy. The big question laid down in this research is how todraw an effective policy line and its implementation. To achieve this it willrequire an extensive scrutiny into the tools and strategies in use and ananalysis of the emerging trends, the need of innovative thinking to develop amodel code for India – WTO interface. The World Trade Organisation (WTO) was created on January1, 1995 to promote world trade. The multilateral trade agreements include theGeneral Agreement on Tariffs and Trade (GATT) 1994 and its related agreements;the General Agreement on Trade in Services (GATS); and the Trade-relatedIntellectual Property Rights (TRIPS)